FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSAHAAN MELAKUKAN AUDITOR SWITCHING (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2016) - Florentina Florentina Marta Delima BR. Sin; Andreas Andreas; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to examine and analyze the factors that affect the company to do switching auditors with empirical studies on manufacturing companies listed on the Indonesia Stock Exchange 2011 to 2016. Dependent variable in this study is the switching auditor. While the independent variables are the change of management, financial distress, KAP size, audit delay, and qualified audit opinion. Sample are 108 companies selected by using purposive sampling method. Hypothesis testing using logistic regression. The results of this study indicate that the change of management has a positive and significant effect on the switching auditor, financial distress and KAP size has a negative and significant effect on the switching auditor, while the audit delay and the qualified audit opinion have no effect on the switching auditor. Based on the coefficient of determination (R2 ) obtained adjusted R2 0.369. This shows that all independent variables affect the dependent variable 36.9% while the remaining 63.1% influenced by other variables not examined in this studyKeywords: auditor Switching, Purposive Sampling, Logistic Regression And IDX.